Assessment of the sensitivity of diagnostic methods in detecting hemodynamically significant renal artery stenoses - A. M. Erkenova; N. M. Danilov; Yu. G. Matchin; V. V. Kushnir; S. A. Gaman; I. E. Chazova (Евразийский Кардиологический Журнал, 2024)
Objective. Assessment of renal artery stenosis significance in patients with resistant arterial hypertension using non-invasive diagnostic methods and to compare them with the results of selective angiography and methods of physiological assessment of renal artery stenoses.Materials and methods. Prospectively, 156 patients with drug-resistant arterial hypertension and signs of renal artery stenosis detected by doppler ultrasonography of renal arteries were included in the study. Subsequently, 25 patients were excluded from the study due to multiple variant renal blood supply and bilateral renal artery stenosis. The remaining patients (n=131) underwent selective angiography of renal arteries, and 66 of them additionally underwent CTA of renal arteries with intravenous contrast. If the artery narrowing was 90% or more (n=27) in diameter, the stenosis was considered hemodynamically significant and further stenting of the affected artery was performed, and in case of 60-90% stenosis (n=52) additional assessment of functional significance of the stenosis was performed by measuring translesional pressure gradient, fractional blood flow reserve, instantaneous blood flow reserve (iFR) and Pd/ Pa ratio. Results. Among all patients (n=131), in whom the doppler ultrasonography of renal arteries showed signs of unilateral renal artery stenosis, after angiography combined with additional methods of functional significance assessment, hemodynamically significant renal artery stenosis was confirmed in 41% of cases (n=54). Thus, the sensitivity of doppler ultrasonography of renal arteries in detection of hemodynamically significant stenoses was 74%, prognostic value of positive 78% and negative result 64% (p<0,001). According to CTA (n=66) renal artery stenosis was confirmed in 56 patients. The results of CTA of renal arteries in 88% of cases coincided with the results of selective angiography, and using additional functional methods hemodynamically significant stenosis was confirmed in 32 (48%) patients. The sensitivity of CTA in detection of hemodynamically significant stenoses of renal arteries was 69%, specificity 91%, prognostic value of positive and negative results was 91 and 68% respectively. According to selective angiography, out of 131 patients, 24 patients had no renal artery stenosis, 28 patients had stenosis <60%, 27 patients had renal artery stenosis >90% and 52 patients had stenosis 60-90%. Patients with stenosis <60% were not considered candidates for renal artery stenting.